Percepções de professores de Educação Física em início de carreira - Anselmo, André Luis dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The present proposal of research emerged after informally identifying that some professionals graduated in Physical Education degree, abdicated the teaching career in its initial phase. This research is part of the research on the entrance into the teaching career and the motivation to remain in the educational area, it is justified by the high number of professionals who, after graduating, give up the profession to follow other paths, often by the lack of preparation to face the difficulties of this initial phase of the career. The aim of the research was to analyze the perceptions of newly formed and early career Physical Education teachers in relation to: being a Physical Education teacher; relevance of the discipline in the school context; society's view of the area; academic training and teaching performance. To analyze the implications of such perceptions on the motivation to remain in the teaching career in Physical Education. The methodology used presents a qualitative approach, with data collection through semi-structured interviews, with personal and socio-professional contexts. Participated in the research eight Physical Education teachers with up to 7 years of training and 5 years of teaching in basic education.It was found that the teachers in this early stage of the career, do not present a clear definition about the purposes of Physical Education School, but they consider it important to work all the dimensions of the student - affective, social, cognitive and motor.The reports were documented and analyzed according to the understanding of the literature consulted. It was found that the teachers in this early stage of the career, do not present a clear definition about the purposes of Physical Education School, but they consider it important to work all the dimensions of the student - affective, social, cognitive and motor... (Complete abstract electronic acess below)

A presente proposta de pesquisa surgiu após identificar, informalmente, que alguns profissionais formados em licenciatura em Educação Física, abdicaram da carreira docente em sua fase inicial. Deste modo, esta pesquisa insere-se no âmbito das investigações sobre o ingresso na carreira docente e as motivações para permanecer na área educacional. Justifica-se esse tema pelo alto número de profissionais que, depois de formados, abdicam da profissão para seguir outros caminhos, muitas vezes pela falta de preparo para enfrentar as dificuldades desse período. O objetivo do estudo consistiu em analisar as percepções de professores de Educação Física recém-formados e em início de carreira em relação a: ser professor de Educação Física; relevância da disciplina no contexto escolar; visão da sociedade sobre a área; formação acadêmica e atuação docente; as implicações de tais percepções na motivação em permanecer na carreira docente em Educação Física. A metodologia utilizada fundamentou-se na abordagem qualitativa, com coleta de dados por meio de entrevistas semiestruturadas, com questões pessoais e de contexto sócio-profissionais. Participaram da pesquisa oito professores de Educação Física com até sete anos de formação e cinco anos de atuação docente na educação básica. Os relatos foram documentados e analisados em diálogo com a literatura. Constatou-se que os docentes, nessa fase inicial da carreira, não apresentam uma nítida definição sobre as finalidades da Educação Física Escolar, mas julgam ser importante trabalhar todas as dimensões do aluno - afetivo, social, cognitivo e motor. Consideram ser importante trabalhar com a conscientização dos benefícios provenientes da prática de exercícios/atividade física, principalmente em prol da saúde, mas sempre levando em consideração a formação integral do aluno... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Carreiras e oportunidades; Professores de educação fisica; Educação fisica